A Major Regional Measles Outbreak: Description of Hospitalized Cases in 2017–2018 at Bordeaux University Hospital, France. (17th August 2020) - Barthod, Laure; Fourgeaud, Jacques; Puges, Mathilde; Rogues, Anne-Marie; Coppry, Maïder; Sarlangue, Jean; Boyer, Alexandre; Neau, Didier; Vabret, Astrid; Dina, Julia; Lafon, Marie-Edith; Cazanave, Charles
Abstract: Background: Measles remains endemic worldwide, despite current vaccination recommendations, and is associated with high morbidity and mortality rates. We describe all cases hospitalized in Bordeaux University Hospital (BUH), the starting point of a national significant measles outbreak in 2017–2018. Methods: In this retrospective study, we included all patients hospitalized in BUH from September 1, 2017, to May 31, 2018. Inclusion criteria were age >1 year, clinical symptoms, and biological confirmation by measles immunoglobulin M or measles reverse transcription polymerase chain reaction positivity. Results: We included 171 patients. Most patients were immunocompetent; only 19% had preexisting medical histories. Most patients had rash and fever (97%), but some cases were atypical and difficult to diagnose. Köplik's spots were reported in 66 cases (38%). The most frequent biological markers were blood inflammation markers (96%) and lymphopenia (81%). Unexpectedly, we found hyponatremia (<135 mmol/L) in 40% of patients. We identified peaks in January and March, corresponding to 76 D8 genotypes and 28 B3 strains. The following complications were reported in 65 patients (38%): pneumonia, hepatitis, and keratitis; 10 had neurological symptoms. One patient had Guillain-Barré syndrome, and a young immunocompromised patient died from measles inclusion-body encephalitis. Most of the patients (80%) had not been correctly vaccinated, including 28 health care workers. Some patients (n = 43, 25%) developed measles despite having plasma IgG. These included 12 possible vaccination failure cases. Conclusions: During the BUH outbreak, measles was often complicated and sometimes atypical. Vaccination coverage was dramatically insufficient. We also describe vaccination failure cases that must be better investigated.